Dusting off Neogene glyptodonts (Xenarthra, Cingulata, Propalaehoplophorinae) beyond Argentinian Patagonia - Martini, Gastón Andrés (2024)
Propalaehoplophorinae glyptodonts have an extensive Paleogene and Neogene record, primarilyconfined to Patagonia, Argentina, especially in the Santa Cruz Formation (Miocene). Extra-Patagonian records are scarce and include: 1) for the Paleogene in Argentina from the Fray Bentos (Entre Ríos Province) and Agua de la Piedra (Mendoza Province) formations (Oligocene), assigned to Propalaehoplophorinae indet.; 2) for the Neogene in Argentina from the Chinches Formation (San Juan Province; Miocene), assigned to Asterostemma barrealense, and from the Aisol Formation (Mendoza Province; Miocene), assigned to Propalaehoplophorinae indet.; 3) for the Neogene in Bolivia from Quebrada Honda, assigned to cf. Asterostemma and Propalaehoplophorus andinus, and in Brazil from Río Acre (Miocene) assigned to Asterostemma sp. Here, we reviewed the holotype (only specimen) of Asterostemma barrealense (MCNAM PV 154, Museo de Ciencias Naturales y Antropológicas "J.C. Moyano", Colección Paleovertebrados, Mendoza), from Los Patos River, west Barreal (San Juan, Argentina) according to Rusconi, and report a new specimen (PVSJ 1117, Museo de la Universidad de San Juan, San Juan) of extra-Patagonian Propalaehoplophorinae glyptodont (same locality), corresponding to the lower levels of the Chinches Formation (Miocene). The holotype is a fragment of an antero-dorsal carapace (six osteoderms, two incomplete). These osteoderms have a finely dotted surface and a "rosette" pattern, with a rounded central figure towards the posterior margin, and a transverse major axis. The peripheral figures are smaller laterally and posteriorly, with prominent anterior figures. Shallow central and radial grooves obscure the peripheral figures. Small foramina are at the groove intersections, more numerous on the central grooves. Dorsal foramina are deeper and small, at the margins between osteoderms, which are regular with minimal porosity. The new specimen (PVSJ 1117) is a fragment of a postero-lateral carapace (21 osteoderms, 16 incomplete). These osteoderms also have a "rosette" pattern with a prominent, rounded central figure, slightly posteriorly displaced, and a vertical major axis. Quadrangular peripheral figures vary in size, with reduced lateral figures and less reduced posterior ones. Each osteoderm has two significantly larger anterior peripheral figures compared to the less visible posterior and lateral ones, lacking accessory figures. Well-marked central and radial grooves create pronounced relief and moderate porosity, making the rosette pattern evident. The osteoderms have regular margins with minimal porosity, no foramina. Morphologically, both specimens (MCNAM PV 154 and PVSJ 1117) lack diagnostic characters, suggesting they should be assigned to Propalaehoplophorinae gen. et sp. indet.